The Implementation of the Tabayyun Concept in Learning Islam to Enhance Attitudes of Religious Moderation - Dedi Masri; Pandu Prabowo Warsodirejo (AL-ISHLAH: Jurnal Pendidikan, 2023)
Religious moderation refers to a moderate approach, an inclusive approach to Islam, or an open-minded approach to religion. Because it is simpler for religious sects and teachings to spread in society through social media and other religious studies that are not always authentic, Tabayyun's attitude toward religious moderation is extremely important. For this reason, people must exercise caution and double-check their assumptions before learning anything. This study aims to analyze how the Tabayyun concept is used in Islamic education to promote religious moderation. This study employed a qualitative descriptive research methodology. Interviews and observational techniques were used by researchers to gather data. The study results demonstrate that there are various Tabayyun concepts, such as a) Tabayyun based on Rationality, b) Tabayyun with an Objective Attitude, and c) Tabayyun through Empirical Attitudes, that can be incorporated into Islamic Religious Education learning. Additionally, the concept of Tabayyun in Islamic religious education enhances the attitude of religious moderation by fostering harmony between educators, students, the community, and the environment to produce a tranquil and secure atmosphere free from numerous dangers. Therefore, it may be inferred that the Tabbayun concept can be included in Islamic instruction to enhance students' attitudes toward religious moderation.